Mortality and Antifeedant Effects of some Jamu Waste Extract on Larvae of Spodoptera litura - Ikawati, Silvi; Silalahi, Fuji Nafratilova; Izzah, Annisa Nurul; Choliq, Fery Abdul; Mustofa, Oki (AGRIVITA Journal of Agricultural Science, 2025)
The amount of herbal waste in Indonesia is quite high, so it needs to be managed to reduce the amount and increase the value of benefits. One way is to utilize it as a botanical insecticide. This study aims to determine the effect and concentration of herbal waste extract that is effective on mortality and inhibition of feeding activity of Spodoptera litura (F.) (Lepidoptera: Noctuidae). Larvae of S. litura are one of the pests in mustard plants. The extraction method used a maceration method with ethanol solvent. Research using four types of herbal waste extracts with a leaf dipping method. The results show that four extracts affect increased mortality and inhibition of the feeding activity of S. litura larvae. The value of LC50 is at 60 HAA, LT50, and the inhibition of eating activity at a concentration of 36% by ginger jamu waste extract is 29%, 27 hours, and 64%. In contrast, curcuma jamu waste extract was 25%, 24 hours, and 68%, respectively. For LC50 at 72 HAA, LT50 and inhibition of eating activity at a 50% concentration of galangal jamu waste extract was 17%, 14 hours, and 43%. While turmeric jamu waste extract was 17%, 16 hours, and 42% respectively.